2010
DOI: 10.1016/j.acra.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Lung Ventilation and Microstructure in an Animal Model of Idiopathic Pulmonary Fibrosis Using Hyperpolarized Gas MRI

Abstract: RATIONALE AND OBJECTIVES-The use of hyperpolarized 3 He MRI as a quantitative lung imaging tool has progressed rapidly in the past decade, mostly in assessment of the airways diseases COPD and asthma. This technique has shown potential to assess both structural and functional information in healthy and diseased lungs. In this study, we apply the regional measurements of structure and function to a bleomycin rat model of interstitial lung disease. MATERIALS AND METHODS-MaleSprague Dawley rats (300-350 g) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…On the other hand, the mean r values were less in bleomycin-instilled rats than in both the controls and LPS-instilled rats, but only significantly different from the control rats. Similarly, reduced fractional ventilation values were observed in a study involving fractional ventilation mapping using HP 3 He MRI in bleomycin-instilled rats, and it was suggested that a decrease in lung compliance was a major factor in diminishing alveolar expansion and ventilation (44). The fractional ventilation gradients from control rats agreed with expectations from the literature, where rats in the supine position had a greater ventilation in more dependent regions of the lung (34).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the mean r values were less in bleomycin-instilled rats than in both the controls and LPS-instilled rats, but only significantly different from the control rats. Similarly, reduced fractional ventilation values were observed in a study involving fractional ventilation mapping using HP 3 He MRI in bleomycin-instilled rats, and it was suggested that a decrease in lung compliance was a major factor in diminishing alveolar expansion and ventilation (44). The fractional ventilation gradients from control rats agreed with expectations from the literature, where rats in the supine position had a greater ventilation in more dependent regions of the lung (34).…”
Section: Discussionsupporting
confidence: 80%
“…An alternative method for identifying tissues at risk for disease progression is needed in order to better stage and triage patients eligible for emerging new therapies [212]. Initial efforts using HP 3 He MRI focused on the feasibility of measuring ventilation changes [213] to better detect early progression in fibrotic lung disease, but these efforts had limited success for several reasons. First, ventilation is secondary to the underlying process of fibrotic injury and therefore an indirect measure of severity; and second, few therapies were available to treat these patients beyond simply limiting environmental exposure.…”
Section: Applications Of Hyperpolarized Gas Mri To Pre-clinical Anmentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) and fractional ventilation are commonly used metrics to evaluate lung function and structure. Hyperpolarized 3 He MRI analysis has shown that BLMor radiation-exposed rats had significantly decreased fractional ventilation and ADC of 3 He compared with control animals (23,24). Furthermore, areas of decreased ADC in radiation-treated rats correlated with lung fibrosis identified by histological analysis (24).…”
Section: Hyperpolarized Gas-enhanced Mrimentioning
confidence: 98%